Rancang Bangun Smart Coffee Dry-Huller Machine Tenaga Surya Berbasis IoT dengan Inovasi Sinar UV sebagai Penghigienis - Akbar, Ikhwanul Fajri Al; Hidayatullah, Syarif; Baihaqi, Ihsan Hendrawan; Mubarakah, Fathimah Nabilah; Maulidiyah, Fany Dwi; Ulma, Zeni (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Dry coffee processing greatly affects the quality of the coffee produced. The obstacle faced in coffee processing is that the time and energy required are still too large. In addition, the results of the peeling capacity of dry coffee skins are not good because they are too slow. Drying is very important in coffee processing, without good drying the quality of the coffee beans will not be maximized. Based on the description of the problem, the application of the Smart Coffee Dry-Huller Machine technology aims to automatically peel and dry coffee beans which are environmentally friendly at an affordable cost for coffee farmers as well as hygienic coffee beans. The method used in designing the tool is by going through the pre-production stage, the production stage and the post-production stage. The energy potential used in the huller is 2,04 watts in standby mode, 47 watts in low mode, 52 watts in medium mode, and 55 watts in high mode, while the energy potential in the dryer is 357 watts and can reduce the water content by 10%/hour by maximum temperature of 53,9oC.